Cigarette smoking is associated with Herpesviruses in persons with and without serious mental illness - Faith Dickerson; Emily Katsafanas; Andrea Origoni; Theresa Newman; Kelly Rowe; Rita S. Ziemann; Kamal Bhatia; Emily Severance; Glen Ford; Robert Yolken (PLoS ONE, 2023)
Introduction Herpesviruses are recognized as major causes of human diseases. Following initial infection, Herpesviruses can undergo cycles of reactivation controlled largely by the immune system. Cigarette smoking is an important modulator of the immune system particularly in individuals with serious mental illness where smoking is associated with increased rates of cardiopulmonary diseases and mortality. However, the effect of smoking on Herpesviruses has not been extensively studied. Methods In this nested cohort study, cigarette smoking was assessed in 1323 persons with serious mental illness or without a psychiatric disorder ascertained in a psychiatric health care system and the adjacent community. Participants provided a blood sample from which were measured IgG class antibodies to five human Herpesviruses: Cytomegalovirus (CMV), Epstein Barr Virus (EBV), Herpes Simplex Virus-Type 1 (HSV-1); Varicella Zoster Virus (VZV); and Human Herpes Virus-Type 6 (HHV-6). The associations between smoking variables and antibody levels to the Herpesviruses were analyzed among diagnostic groups in multiple regression models adjusted for age, sex, and race. Results Current smoking was significantly associated with higher levels of antibodies to CMV (coefficient .183, 95% CI .049, .317, p<.001, q<.007) and the three EBV proteins (EBV NA –(coefficient .088, 95% CI .032, .143, p = .002, q<.014; EBV Virion – coefficient .100, 95% CI .037, .163, p = .002, q<.014; and EBV VCA – coefficient .119, 95% CI .061, .177, p = .00004, q<.0016). The amount of cigarettes smoked was also correlated with higher levels of antibodies to the three EBV proteins. Interaction analyses indicated that the association between cigarette smoking and levels of antibodies to CMV and EBV was independent of diagnostic group. Cigarette smoking was not significantly associated with the level of antibodies to HSV-1, VZV, or HHV-6. Conclusions Individuals who smoke cigarettes have increased levels of IgG antibodies to CMV and EBV. Cigarette smoking may be a contributory factor in the relationship between CMV, EBV and chronic somatic disorders associated with these viruses.